STRATEGI PENINGKATAN KETAHANAN PANGAN DALAM MEMINIMALISASI STUNTING DI KABUPATEN SUKABUMI - Riajaya, Hadi; Munandar, Adis Imam (Jurnal AGRISEP, 2020)
Food security has becoming strategic issue in Sukabumi District in view of this district still having stunting prevalence 37%. In other word, one of three children in Sukabumi District having stunting. This research aims to maping the level of society food resilience and to formulating the strategy of increasing food security in minimizing case of stunting in Sukabumi District. The method applied in this reasearch is descriptive qualitative which combined with EFE (External Factor Evaluation) and IFE (Internal Factor Evaluation) analysis in one formula SWOT (Strength Weakness Opportunity Threat). Research also used an approach of Global Food Security Index; and Food Security and Vulnerability Atlas. The results of this research are considered from affordability dimension, whole society could afford it; availability dimension, amount of food availability has fulfill the ideal standard; while quality and safety dimensions heve not fulfill the ideal standard. Sukabumi District are having 168 villages that food insecurity. The appropriate strategy of increasing food security in minimizing stunting is Diversification Strategy, which implementing through: (1) food diversification; (2) optimilizing food and livestock availability; (3) providing employment in agriculture areas; and (4) restraining the conversion of agricultural land.